Economic evaluation of long-term impacts of universal newborn hearing screening. (2nd January 2017) - Chiou, Shu-Ti; Lung, Hou-Ling; Chen, Li-Sheng; Yen, Amy Ming-Fang; Fann, Jean Ching-Yuan; Chiu, Sherry Yueh-Hsia; Chen, Hsiu-Hsi
Abstract: Objective: Little is known about the long-term efficacious and economic impacts of universal newborn hearing screening (UNHS). Design: An analytical Markov decision model was framed with two screening strategies: UNHS with transient evoked otoacoustic emission (TEOAE) test and automatic acoustic brainstem response (aABR) test against no screening. By estimating intervention and long-term costs on treatment and productivity losses and the utility of life years determined by the status of hearing loss, we computed base-case estimates of the incremental cost–utility ratios (ICURs). The scattered plot of ICUR and acceptability curve was used to assess the economic results of aABR versus TEOAE or both versus no screening. Study sample: A hypothetical cohort of 200, 000 Taiwanese newborns. Results : TEOAE and aABR dominated over no screening strategy (ICUR = $-4800.89 and $-4111.23, indicating less cost and more utility). Given $20, 000 of willingness to pay (WTP), the probability of being cost-effective of aABR against TEOAE was up to 90%. Conclusions: UNHS for hearing loss with aABR is the most economic option and supported by economically evidence-based evaluation from societal perspective.